Financial Literacy and Borrowing Practices of School-based Multi-purpose Cooperative Members in Bacolod City - Christian James T. Perez; Alma B. Lopez (Philippine Social Science Journal, 2020)
Financial literacy is the possession of knowledge and a basic understanding of personal financial matters in terms of borrowing, saving, and investment effectively for a lifetime financial security.  Its concept plays an essential role, especially to those who engage in borrowings. This study aimed to assess the level of financial literacy and borrowing practices of school-based multi-purpose cooperative members in terms of employment designation, amount of capital stock, and the number of dependents.  Specifically, it determined if there is a significant difference in the level of financial literacy and borrowing practices of multi-purpose cooperative members when grouped according to the aforementioned variables.